CBMT-13. UNRAVELLING METABOLISM OF GLIOBLASTOMA USING MASS SPECTROMETRY IMAGING. (5th November 2018) - Upendra Rao, Jyotsna; Gibson, Katherine; Hamm, Gregory; Wright, Alan; Fala, Maria; Mair, Richard; Goodwin, Richard; Brindle, Kevin
Abstract: INTRODUCTION: Glioblastoma Multiforme (GBM) is the most frequent malignant brain tumour in adults. The dismally low survival rates require novel diagnostic and therapeutic approaches. Understanding the tumour metabolic landscape in relation to its microenvironment is paramount. To address this issue, we have used high-resolution Mass Spectrometry Imaging (MSI). METHODS: A female wistar rat implanted intracranially with C6-GBM cells was infused with [U- 13 C]glucose (a bolus of 0.4 mg/g body weight followed by infusion with 0.012 mg/g/min at 300 µL/h for 2 h) at 15 days post cell implantation. The presence of tumour at this point was confirmed in a T2 -weighted magnetic resonance image. Post-infusion, the rat brain was rapidly excised and fixed by rapid freezing in liquid nitrogen. Coronal cryosections were subjected to desorption electrospray ionization (DESI) MSI. The mass-to-charge ( m/z ) ratios of 13 C-labelled and unlabelled metabolites were compared between different brain regions using unsupervised spatial clustering. Naïve rat brain (not infused with [U- 13 C]glucose) was used as a control for natural abundance 13 C. RESULTS: An increase in circulating blood glucose levels from 8 to 9.5 mmol/L was observed at the end of [U- 13 C]glucose infusion. Unsupervised clustering of metabolite m/z ratios distinguished different regions of the brain and normal brain from tumour. The profile of metabolite m/z ratios also showed intra-tumoural metabolite heterogeneity with differences between tumour boundary and core regions. CONCLUSIONS: These results demonstrate that C6-GBMs are metabolically heterogeneous and different from surrounding brain tissue. MSI can thus help unravel spatial differences in tumour metabolism. Comparison of MSI data to histological staining of brain sections can yield additional information about the relationship between the tumour and its microenvironment.